2022
DOI: 10.1177/2156759x221137287
|View full text |Cite
|
Sign up to set email alerts
|

Pornography Use and Sexting Trends Among American Adolescents: Data to Inform School Counseling Programming and Practice

Abstract: To better inform school counseling programming and practice, we assessed trends related to pornography use and sexting behaviors among adolescents. Approximately 53% of the sample had seen pornography, with an average age of 11.5 years old at first exposure. Almost 15% of adolescents had sent a sext and 24.3% had received a sext. The correlation between pornography use and sending a sext was significant. We discuss gender and racial differences and implications for school counselors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Previous research has reported that sexual characteristics, such as online pornography use ( Giordano et al, 2022 ; Morelli et al, 2017 ) and sexual experience ( Barrense-Dias et al, 2017 ), are strongly associated with sexting. Although there has been no direct research on sexting among Cambodian youths, previous studies have reported that Cambodian youths who take pictures on their mobile phones or exchange text messages with the opposite sex are more likely to engage in sexual intercourse ( Pahn & Yang, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported that sexual characteristics, such as online pornography use ( Giordano et al, 2022 ; Morelli et al, 2017 ) and sexual experience ( Barrense-Dias et al, 2017 ), are strongly associated with sexting. Although there has been no direct research on sexting among Cambodian youths, previous studies have reported that Cambodian youths who take pictures on their mobile phones or exchange text messages with the opposite sex are more likely to engage in sexual intercourse ( Pahn & Yang, 2019 ).…”
Section: Discussionmentioning
confidence: 99%